(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Bangladesh experienced four major waves of COVID-19, the first one of which transpired in March of 2020. From its early onset the government of Bangladesh has taken several precautionary measures which include generating public awareness and adherence to appropriate knowledge, attitude and practice towards the global pandemic. The study, conducted in October 2022 attempted to explore the level of knowledge, attitude and practice towards COVID-19 among the residents of Nagarkanda upazila of Faridpur district. Most of the participants learned about COVID-19 through mass media (49.50%), with 87% believing in its preventability and 80% being aware of the minimum distance requirements. They believed the virus spreads through direct transmission during coughing (93%), contact with infected individuals (86%), touching contaminated surfaces (79.5%), and contact with infected animals (49.5%). They identified elderly individuals (95.3%), migrants (78%), pregnant women (66.7%), those with underlying health conditions (60%), and children (59%) as the most vulnerable groups. However, the majority did not dismiss the pandemic as a myth, with 90.70% understanding the importance of isolation. Treatment options mentioned included vaccination (65%), specific medications (41%), supportive care (39.30%), and herbal remedies (25.70%). A large majority (91.70%) had already received the COVID-19 vaccine, while 8% had not been immunized, and 0.30% were unaware of vaccination efforts. The findings suggest that an adequate amount of health education interventions should be directed to the particularly vulnerable rural populations at high risk of contracting COVID-19. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):91-96